Kyrgyz Republic : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper reviews economic developments in the Kyrgyz Republic during 1995-97. Significant progress has been achieved in establishing macroeconomic stability since 1994. Inflation has fallen sharply over 1992-97, and projections indicate that the 17 percent targeted for the year will be achieved. After a massive output decline during 1991-95, real GDP started to increase in late 1995 and showed solid growth in 1996 and during the first half of 1997. The budget deficit was halved during 1995-96 and is targeted to decline further in 1997, financed mostly through external assistance.